2019
DOI: 10.1002/jcph.1539
|View full text |Cite
|
Sign up to set email alerts
|

Use of Propofol Plus Dexmedetomidine in Patients Experiencing Severe Alcohol Withdrawal in the Intensive Care Unit

Abstract: Alcohol abuse and alcohol withdrawal syndrome are major problems in the United States. This retrospective chart review assessed efficacy and safety of propofol plus dexmedetomidine used in combination as adjunctive therapy to benzodiazepines compared with either agent used alone in the treatment of severe alcohol withdrawal. Patients admitted to the intensive care unit and experiencing severe alcohol withdrawal between September 1, 2015 and September 30, 2018 were assessed for eligibility. Primary end points w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…There is some support for cognitive preservation during dexmedetomidine infusion 61–63. Of note, dexmedetomidine is not an antiepileptic medication and other agents may be necessary for this indication 64. With the appropriate level of monitoring, it has been used in both intubated and non-intubated patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is some support for cognitive preservation during dexmedetomidine infusion 61–63. Of note, dexmedetomidine is not an antiepileptic medication and other agents may be necessary for this indication 64. With the appropriate level of monitoring, it has been used in both intubated and non-intubated patients.…”
Section: Discussionmentioning
confidence: 99%
“…This activation inhibits firing, thereby inducing sedation and anxiolysis 1. Of note, propofol binds at a different site of the GABA A receptor than benzodiazepines, and, hence, is often used in benzodiazepine refractory cases 60 64. Propofol also reduces glutamate activity, thereby preventing seizures, inhibits NMDA glutamate receptors, and is thought to inhibit other amino acids that may be upregulated in DTs 1 59 60 69.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two trials even suggested a trend to longer LOS if dexmedetomidine was Visc Med 2020;36:160-166 DOI: 10.1159/000507595 added to BZO therapy [42], especially for AWS treatment in medical intensive care unit (ICU) patients [43]. However, in combination with propofol, patients treated in the ICU with severe AWS had a shorter time to extubation and ICU LOS [44].…”
Section: Therapy Of Suspected Aws In the Perioperative Settingmentioning
confidence: 99%
“…A systematic review identified the most common approach to management of AWS in critically ill patients was primarily benzodiazepine (BZD)-based. 5 However, phenobarbital, 7,8 dexmedetomidine, 9,10 or propofol 11 may be considered for BZD-sparing effects or for those on mechanical ventilation. Other agents, such as baclofen, 12 valproic acid derivatives, 13 gabapentin, 14 ketamine, 15 clonidine, 16 and antipsychotics 17 have also been evaluated.…”
Section: Introductionmentioning
confidence: 99%